2003
DOI: 10.1523/jneurosci.23-06-02102.2003
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Sodium Channels and AnkyrinG Occupy a Different Postsynaptic Domain from Acetylcholine Receptors from an Early Stage of Neuromuscular Junction Maturation in Rats

Abstract: Spatial segregation of membrane proteins is a feature of many excitable cells. In skeletal muscle, clusters of acetylcholine receptors (AChRs) and voltage-gated sodium channels (Na V 1s) occupy distinct domains at the neuromuscular junction (NMJ). We used quantitative immunolabeling of developing rat soleus muscles to study the mechanism of ion channel segregation and Na V 1 clustering at NMJs. When Na V 1s can first be detected, at birth, they already occupy a postsynaptic domain that is distinct from that oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…We found that ankyrin G was clustered in close proximity to the NMJ and was found at the muscle membrane but not actually at the NMJ (Fig. 6C), suggesting that at this time of development of the system, the protein localization has not reached a fully mature status as previously reported in vivo (Bailey et al, 2003), further supporting this method for the study of different phases of NMJ maturation.…”
Section: Formation Of Nmjssupporting
confidence: 82%
See 1 more Smart Citation
“…We found that ankyrin G was clustered in close proximity to the NMJ and was found at the muscle membrane but not actually at the NMJ (Fig. 6C), suggesting that at this time of development of the system, the protein localization has not reached a fully mature status as previously reported in vivo (Bailey et al, 2003), further supporting this method for the study of different phases of NMJ maturation.…”
Section: Formation Of Nmjssupporting
confidence: 82%
“…The following antibodies were used: mouse anti-βIII tubulin (R&D systems, MAB1195, clone #TuJ1, 1/400), rabbit anti-ryanodine receptor (Braubach et al, 2014) (Millipore, AB9078, 1/200), goat anti-VaChT (Atasoy et al, 2014) (Millipore, ABN100, 1/100), goat anti-ChAT (Sümbül et al, 2014) (Millipore, AB144, 1/100), chicken anti-neurofilament H (NFH) (Wainger et al, 2015) (Millipore, AB5539, 1/400), mouse anti-dihydropyridine receptor (DHPR) (Bradley et al, 2014) (Abcam, Ab2864, 1/400), mouse anti-synaptotagmin (Wong et al, 2014) (Abcam, ab13259 clone ASV30, 1/100), mouse anti-α-actinin (Falcone et al, 2014) (Sigma-Aldrich, A5044 clone BM-75.2, 1/500), mouse anti-sodium channel pan (Bailey et al, 2003) (Sigma-Aldrich, clone K58/35, S8809, 1/100), mouse anti-ankyrin (Bailey et al, 2003) (Thermo Scientific, 33-8800, clone 4G3F8, 1/100), mouse antibassoon (Jing et al, 2013) (Abcam, ab82958, 1/100), rabbit anti-glial fibrillary acidic protein (GFAP) (Achtstätter et al, 1986) (Dako, Z0334, 1/100), mouse anti-oligodendrocytic marker O4 (Paintlia et al, 2004) (Sigma-Aldrich, O7139, clone O4, 1/400), rabbit anti-MuSK (serum T194, gift from Markus Ruegg, Biozentrum, University of Basel, Switzerland, 1/500), mouse anti-rapsyn [Abcam, ab11423 (1234), 1/200], mouse antiSyne1 (clone 8c3, gift from Glenn Morris, Keele University, UK, 1/200).…”
Section: Primary Antibodiesmentioning
confidence: 99%
“…Ankyrin-G may also be required for targeting of Na v 1.1 to specialized sites in neurons and of Na v 1.4 to the neuromuscular junction in skeletal muscle. It is of interest in this regard that ankyrin-G is located at the neuromuscular junction in the postsynaptic domain enriched in Na v channels (16,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction maintains the polarized distribution of Na + /K + ATPase in epithelial cells (Nelson and Veshnock, 1987). At developing rat NMJs, voltage-gated sodium channels (Na v 1) and ankyrinG occupy a distinct postsynaptic domain from the AchR clusters (Bailey et al, 2003). At the C. elegans NMJ, the sodium channel could be replaced by Na + /K + ATPase, because there is no candidate gene corresponding to a voltage-gated sodium channel in the C. elegans genome.…”
Section: Possible Mechanisms For Nachr Clustering By Na + /K + Atpasementioning
confidence: 99%